The Correlation between Teaching-Learning Process and Teacher Competency Assessments - Mardiah Mardiah (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Teacher competency assessment plays a crucial role in providing valuable insights into the expected outcomes of the teaching profession. By employing such assessments, miscommunication regarding the desired quality of a teacher’s work can be minimised while enhancing teacher productivity through constructive feedback for those who excel. Furthermore, the implementation of teacher competency assessments aims to acquire valid, up-to-date, and authentic evidence, specifically in areas related to the learning process and a teacher’s proficiency in pedagogy, social skills, personality traits, and professional attributes. This research explores the significance of the correlation between the teaching-learning process and teacher competence assessment. The author adopts a literature-based approach to comprehensively review the relationship between these two components to accomplish this. This approach enables a comprehensive understanding of how learning and the assessment of teacher competence are interconnected. The gathered data will subsequently undergo analysis using a content analysis method, which seeks to identify recurring themes and patterns within the existing literature related to the relationship between the teaching-learning process and teacher competence assessment.